2023
DOI: 10.1097/dad.0000000000002366
|View full text |Cite
|
Sign up to set email alerts
|

TERT Promoter Mutational Analysis as an Ancillary Diagnostic Tool for Diagnostically Challenging Melanocytic Neoplasms

Abstract: Telomerase reverse transcriptase promoter mutations (TPMs) have been shown to be common in melanoma and uncommon in benign nevi. To assess the use of TPMs as an ancillary diagnostic tool, we report the concordance of the TPM status with the final diagnosis in clinical cases with distinct differential diagnostic scenarios: dysplastic nevus versus melanoma, atypical Spitz nevus versus melanoma, atypical deep penetrating nevus (DPN) versus melanoma, and atypical blue nevus versus malignant blue nevus. In a contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Melanomas arising from congenital nevi may be an exception to this rule. In a recent case report and a recently published study, it was shown in the differentiation of benign proliferating nodules and melanomas arising from congenital nevi that the latter express an increased amount of PRAME (Boutko et al., 2023; Gill et al., 2021). Our data also support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melanomas arising from congenital nevi may be an exception to this rule. In a recent case report and a recently published study, it was shown in the differentiation of benign proliferating nodules and melanomas arising from congenital nevi that the latter express an increased amount of PRAME (Boutko et al., 2023; Gill et al., 2021). Our data also support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that the use of PRAME in the setting of spitzoid tumors is of limited value (Raghavan, Wang, et al., 2020). In contrast, a recent publication found a possible role of PRAME in the differentiation of benign proliferating nodules of melanomas at the base of congenital giant nevi (Boutko et al., 2023).…”
Section: Introductionmentioning
confidence: 95%
“…H3K27 trimethylation (H3K27me3), a well-known epigenetic gene silencer that can inhibit transcription, has been observed to have decreased expression in melanomas arising from CMN but is retained or only mildly reduced in PNs. 42 43,44 They found that anti-PRAME was diffusely positive within the melanoma while negative within PNs most of the time. Of note, the three technologies mentioned above should only be regarded as supplementary tools to other assessments rather than definitive tests of malignancy as they are not entirely specific.…”
Section: Proliferative Nodulesmentioning
confidence: 99%
“…and Boutko et al. successfully applied the preferentially expressed antigen in melanoma (PRAME) as a helpful diagnostic tool in rendering a diagnosis in atypical melanocytic proliferations 43,44 . They found that anti‐PRAME was diffusely positive within the melanoma while negative within PNs most of the time.…”
Section: Complications Of Cmnmentioning
confidence: 99%